Mood disorders in women with premature ovarian insufficiency - Słopień, Radosław (Menopause Review/Przegląd Menopauzalny, 2018)
Premature ovarian insufficiency (POI) and related oestrogen deficiency is a cause of many psychological symptoms, including: depression, psychological tension, anxiety, mood lability, loss of libido, feelings of loss of femininity and attractiveness, and decreased self- and sexual esteem. Distress related to POI diagnosis may be even more confusing when POI is diagnosed in relation to serious health complications such as cancer, due to surgery or chemotherapy. Every case of POI requires coordinated medical advice with special attendance of a gynaecological endocrinologist, psychotherapist, and sometimes even a psychiatrist.